Implementing Healthy Life and Self and Environmental Clean on Orphans in Islahul Hidayat Orphanage - Syifa Marwala Difa; Siti Parida (Indonesian Journal of Multidisciplinary Science, 2022)
Clean and healthy living behavior (PHBS) is a step that must be taken to achieve optimal health degrees for everyone including in the foundation. The emergence of various diseases that often affect children aged (5-11 years) is generally related to Clean and Healthy Living Behavior (PHBS). Some children exhibit unhealthy behaviors such as preferring to consume unhealthy foods that are high in fat, sugar, salt, low in fiber, increase the risk of hypertension, diabetes mellitus, obesity, and so on. In addition, it was also found that children who did not brush their teeth when after eating and before going to bed so that their teeth cavities. This condition must be anticipated immediately by improving a healthy lifestyle through PHBS. Based on surveys and interviews conducted with children at Rumah Yatim and Duafa Yayasan Islahul Hayat, Pondok Petir said it did not know how to brush teeth properly and correctly. This community service (PKM) aims to improve the knowledge and degree of health of children in Rumah Yatim and Duafa Yayasan Islahul Hayat, Pondok Petir by counseling to maintain dental health and how to brush teeth properly and mass brushing activities. This PKM activity was carried out in accordance with the planning and lasted for one day. PHBS Dental Health Counseling and The Right Teeth brushing Movement is effective to realize health education to instill PHBS values so that it has the potential as a change agent to promote PHBS both in school, family, and community environments.